If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -3(a + 5) = -16 Reorder the terms: 2 + -3(5 + a) = -16 2 + (5 * -3 + a * -3) = -16 2 + (-15 + -3a) = -16 Combine like terms: 2 + -15 = -13 -13 + -3a = -16 Solving -13 + -3a = -16 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + -3a = -16 + 13 Combine like terms: -13 + 13 = 0 0 + -3a = -16 + 13 -3a = -16 + 13 Combine like terms: -16 + 13 = -3 -3a = -3 Divide each side by '-3'. a = 1 Simplifying a = 1
| 12y+4x=3 | | -16x^2+28x+25=0 | | h=-16t^2+100t+3 | | (3x^2)-x+9=0 | | 6v-8=34 | | .31(x+8)=-19 | | 5(2c+d)6(c+2d)= | | -16x^2+28+25=0 | | -50.00+1.00x=0.80(x-100.00) | | 8x^2-3x+32=0 | | 7=3x-5-7-7 | | 0.10+10=0.35x | | 6+y=2x | | 3=-1t | | 12y-4x=3 | | 0.10+10=0.35 | | 8x+12y=1580 | | 4x-1+12x-17= | | 9-3b+6b= | | (X-4)=-8 | | 11p+7p+4p=27 | | Cscx-secx=0 | | 4x^2=20x-28 | | Y=3x(2x-1)(x+3) | | .10(x+7)=30 | | 18=2g | | .25v-.42=.28v-.25 | | -4(x-3)-13=3(x+2) | | V=(10-2x)(8-2x) | | c(3)=15 | | 2x^2=13x+24 | | 6+2x=-6x-90 |